Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/hepr.13606
|View full text |Cite
|
Sign up to set email alerts
|

Carbon ion radiotherapy for patients with hepatocellular carcinoma in the caudate lobe

Abstract: Aim: The treatment of hepatocellular carcinoma in the caudate lobe (HCCCL) is technically challenging. We aimed to investigate the efficacy and toxicity of carbon ion radiotherapy (C-ion RT) for HCCCL. Methods: Patients with HCCCL treated with C-ion RT at our hospital between January 2011 and December 2018 were evaluated. The total dose was 52.8 or 60 Gy (relative biological effectiveness) in four or 12 fractions depending on the distance between the tumor and the gastrointestinal tract. The survival outcome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…CIRT has also been applied in situations where HCC is located in the caudate lobe. Okazaki et al [ 42 ] reported the results of CIRT in the treatment of HCC located in the caudate lobe. The study demonstrated no local recurrence, and only two instances of grade 2 or 3 late adverse events were observed among the nine patients.…”
Section: Clinical Outcomes Of Cirt For Hccmentioning
confidence: 99%
“…CIRT has also been applied in situations where HCC is located in the caudate lobe. Okazaki et al [ 42 ] reported the results of CIRT in the treatment of HCC located in the caudate lobe. The study demonstrated no local recurrence, and only two instances of grade 2 or 3 late adverse events were observed among the nine patients.…”
Section: Clinical Outcomes Of Cirt For Hccmentioning
confidence: 99%
“…Radiation therapy alone has been used in the treatment of caudate lobe HCC and has shown positive outcomes. 77 , 78 , 79 Other radiation therapy methods, such as stereotactic radiation therapy and selective internal radiation therapy (SIRT), have been used as additional options for local treatment. Brachytherapy can be used for the treatment of residual caudate lobe tumors that cannot be completely ablated.…”
Section: Multidisciplinary Treatmentmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 Thus, CIRT can be safely applied to various patients with localized HCC. 15 , 16 , 17 , 18 , 19 A single-institution retrospective study using propensity score matching (PSM) demonstrated that CIRT resulted in better outcomes than TACE (3-year overall survival rate, 88% in the CIRT group vs 58% in the TACE group). 20 Therefore, CIRT may be a promising treatment option for patients with localized HCC who are ineligible for surgery or RFA.…”
Section: Introductionmentioning
confidence: 99%